Air Zam-Zam dalam Perspektif Hadits dan Sains: Upaya Mendamaikan Agama dan Sains - Roifatul Munawaroh; Jamilatul Hamdiyah; Siti Afita Rustia Ningsih; Faizatul Maula; Alfina Wildatul Fitriyah (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2024)
Zam-zam water is water that appeared in the Nahi Ismail period, long before the birth of the Prophet Muhammad SAW. Zam-zam water has received direct testimony and justification from the Prophet Muhammad as the best water on earth which contains many benefits. Explicitly, the properties of Zam-Zum water are stated in the hadith, which is considered authentic according to the scholars. This article, in an integrative-interconnective manner, tries to examine the existence of Zam-Zam water through a hadith perspective and a scientific perspective. From a hadith perspective, zam zam water will be studied using several hadith critical methodologies, both from the text of the hadith (mam) or the transmitter’s transmission (sanod). Meanwhile, through a scientific approach, zam-zam water will be researched more deeply so that a scientific fact can be found that the substances contained and the molecules that are arranged in zam-zam water are better than other substances or water molecules. This, in this article, will be proven by: the results of research by Masaru Emuto, a water expert from Japan, regarding the natural power of water, the magic of Zam-Zam water, and the beauty of the crystals that Zam-Zam water forms. Jodi, the Prophet Muhammad’s justification for Zam-Zam water is embodied by the truth of modern scientific research facts. So it can be said that the agenda to reconcile religion and science is not in vain.